A recent survey of the mosquito (Diptera: Culicidae) fauna and seasonal human biting activity in the city of Chisinau, Moldova. Issue 31 (14th January 2013) - Sulesco, Tatiana; Toderas, Lidia; Toderas, Ion
No abstract available